Assessment of prognostic predictive value at the mycosis fungoides - A. S. Zhukov; I. N. Telichko; I. E. Belousova; A. V. Samcov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Micosis fungoides is a primary skin lymphoma characterized with indolent disease course and favorable prognosis. Опіу at some patients one can observe aggressive development of the disease to malignant stage with the exracutaneous outspread. the modern data about the prognostic factors are presented in the review. Disclosure of these factors allows to forecast the course of disease. there is given attention to integral estimation of survival rates on the ground of tNMB-staging sand estimation of the CUP-index. Definition of combination of different prognostic factors would allow to create prognostic models enabling to diagnose on the early stages of disease the patients with high risk of progression of mycosis fungoides.